Thrivers : the surprising reasons why some kids struggle and others shine - Borba, Michele (G.P. Putnam's Sons, 2021)
"The bestselling author of UnSelfie explains why the old markers of accomplishment (grades, test scores) are no longer reliable predictors of success in the 21st century -- and offers 7 teachable traits that will safeguard our kids for the future"--